SOCIETAL INNOVATION AND SOCIAL ENTREPRENEURSHIP: A THEORETICAL PERSPECTIVE - Mathushan, P. (University of Jaffna, 2019)
The phenomenon of social entrepreneurship, perhaps designate societal entrepreneurship, acquires lofty attentiveness and prevalence by policy formulators, opinion leaders, and by research scholars as well. Typically, Social entrepreneurship is about generating innovative solutions and resolving social, cultural, and environmental-related problems effectively with an intent to bring a revolution to form the society. Comparatively, the primary significance of business entrepreneurship is generating profit through innovative products and services, conversely social entrepreneurship focusing on creating social value through innovative solutions. The successfulness of social entrepreneurship relies on innovation and innovative ideas and solutions. Notwithstanding it is a process of integrating creative thinking and innovation, having sufficient resources, open doors to consign censorious socio-environmental challenges and problems. Social entrepreneurs concern on transforming systems and practices that are root causes of poverty, wastage, water child education, women issues, agricultural and infrastructure, and environmental issues. The ultimate purpose of social entrepreneurship is promoting, establishing new and ideal ways to improve the world's lives. The fundamental objective of this conceptual paper is to investigate the interrelationship and importance between innovation and social entrepreneurship success through a systematic review of the concurrent review of the literature.
Keywords: Entrepreneurial success; Innovation; Social entrepreneurs; Social innovation; social values.